Examining Forms and Socio-cultural Influences of Violence Against Women and Girls: A Survey on Awareness in Thai Society - Vichitrananda, Sutthana; Anukansai , Kanokkan (NIDA Development Journal, 2023)
This article investigates violence against women and girls (VAWG) by classifying and examining various forms of VAWG. The analysis is informed by two secondary sources of data: existing literature and survey results conducted by NIDA Poll in 2022. The article delves into the influence of socio-cultural dimensions, with a specific focus on gender norms, on the various forms and characteristics of VAWG. These encompass a spectrum of forms, including intimate partner violence; sexual harassment; cyber violence; modern slavery; harmful traditional practices such as honor killing and female genital mutilation; and violence from community or society. The survey results on VAWG awareness within Thai society are presented in this study to enhance the comprehension of the subject matter. The survey findings revealed a notable level of awareness concerning sexual harassment, modern slavery, and harmful traditional practices. However, the perspectives diverged on certain issues such as such as romance scams and intimate partner violence. These insights provide a foundation for the formulation of enhanced strategies to combat and prevent violence against women and girls.